Історико-правові аспекти конституційних основ правового статусу суддів у період національно-визвольної боротьби на початку ХХ століття (1917-1921 роки) - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена аналізу конституційно-правових основ статусу суддів у період національно-визвольної боротьби на початку ХХ століття (1917-1921 роки), визначено фактори, що впливали на їх формування. Досліджено динаміку окремих елементів правового статусу суддів в ході розробки проектів конституційних актів.The article presents a historical analysis of the genesis of the judges legal status in the period of the national liberation struggle in the early twentieth century (1917-1921). The period was characterized by armed confrontation, constant changes of the government forms and the formation of various public entities. Particular attention is paid to the institution of the judges legal status, which was approved and evolved in that period, and at the same time it performed different roles and had various political and legal status, depending on the forms of government. Despite the extremely complex conditions of the adoption of the document and its limitations, and sometimes failure in implementation, we come across normative standards of the institute of constitutional grounding of judges’ legal status in almost all the constitutional and constituent documents. The article claims that in this period certain elements of the legal status of judges had been established, including such as the requirements applied to the judges, the procedure of their election and appointment; the oath of judges; the powers of judges; responsibilities of judges; judges security guarantees.
Historical and Legal Aspects of the Judges’ Legal Status Constitutional Foundations in the Period of the National Liberation Struggle in the Early Twentieth Century (1917- 1921)
Keywords: правовий статус; правовий статус судді; правосуддя; суддя; судова система; legal status; legal status of judges; justice; judge; judicial system